HEDGING AS a POLITENESS STRATEGY IN RESEARCH ARTICLE REVIEWS (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-22-33Metadiscourse in academic communication has been under the analysis of a great number of studies. However, most research was predominantly conducted on English academic texts, while metadiscourse strategies are used in Russian-language academic prose remains understudied and needs to be explored. On the basis of 50 reviews of manuscripts submitted to Russian journals, the present article analyzes types of the lexical realization of hedging as a metadiscourse strategy used by reviewers to mitigate negative evaluations and to show politeness. The study is relevant due to the numerous attempts to reconceptualize the nature of academic discourse and to ascribe it to the interactional rather than informational type of communication. Hedging is used for constructing harmonious relationship between the reviewer and the reviewee. The present study aims to identify lexical items used for hedging in the corpus of research article reviews. When the quantitative analysis reveals that hedging is predominantly realized through the use of verbs and adverbs, the interpretive analysis shows that lexical hedges serve for three pragmatic functions such as shifting the communicative focus, mitigating criticism, and de-intensifying negative evaluations. Hedging is an indicator of the authorial pragmatic competence and is a key to effective communication in the evaluative genres of academic discourse and research articles reviews. It creates a proper balance of negative and positive evaluations, assists in saving face and constructing an image of a competent partner.Keywords: academic discourse, scientific review, hedging, meta-discourse, negative assessment, lexical unit